Fit to Compete : why honest conversations about your company's capabilities are the key to a winning strategy - Beer, Michael (Boston : Harvard Business Review Press, 2020)
"In thirty years of working in corporations, Michael Beer has witnessed how organizational silence has derailed many a strategic objective. When lower-level employees in the organization can't speak truth to power, senior leaders don't hear what they need to hear about their firm's fitness to compete. Employees lose trust in higher-ups and become more resistant to change. In Fit to Compete, Beer presents an antidote to silence--an innovative and highly effective process for holding honest conversations with everyone in your organization. Used by over 150 organizations across the globe, the Strategic Fitness Process has helped leaders in industries as diverse as medical technology, restaurant chains, and pharmaceuticals hear the raw and necessary truth about the sources of misalignment between their strategies and their organizations. In addition to a step-by-step guide, Beer offers detailed and illustrative case studies of companies that have used the Strategic Fitness Process to great effect. He also shows how to apply the process more broadly, to a variety of strategic challenges and at multiple levels throughout the organization"--
Introduction: Why your strategy needs an honest conversation -- Part I. The power of honest conversations: How to lead an honest conversation -- Why honest conversations are transformative -- Part II. How and why honest conversations work: Fit to compete: becoming a corporate Olympian -- Fit to perform: overcoming the 'silent killers' -- "Fit to trust: overcoming hierarchy -- "Fit to adapt: the missing strategic learning and governance process -- Part III. What if honest conversations were the norm?: Corporate stewardship demands honest conversations -- Honest conversations demand courage.
Includes index.
Keywords: Communication in management; Organizational behavior; Honesty; Trust; Organizational effectiveness; Communication in management; Organizational behavior; Honesty